2008
DOI: 10.1080/02770900701840238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Depression and Anxiety on Quality of Life, Health Behaviors, and Asthma Control Among Adults in the United States with Asthma, 2006

Abstract: This research indicates that a multidimensional, integrative approach to health care should be considered when assessing patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
99
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 58 publications
(51 reference statements)
8
99
1
5
Order By: Relevance
“…It is also speculated that depression could directly influence the autonomic nervous system and act on direct respiratory resistance, symptom perception, and AE (36,37). Other studies also report that risk behaviors such as smoking, physical inactivity, obesity, and health-service seeking associated with depression might influence asthma outcomes (38,39). All of these factors may contribute to the association between PD and AE.…”
Section: Discussionmentioning
confidence: 99%
“…It is also speculated that depression could directly influence the autonomic nervous system and act on direct respiratory resistance, symptom perception, and AE (36,37). Other studies also report that risk behaviors such as smoking, physical inactivity, obesity, and health-service seeking associated with depression might influence asthma outcomes (38,39). All of these factors may contribute to the association between PD and AE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there is a strong association between psychiatric disorders and uncontrolled asthma. (9,10,23) Might this association be two sides of the same coin? On the one hand, the higher prevalence of anxiety among patients with uncontrolled asthma might promote mood disorders, which in turn might increase symptom perception in such patients, thereby reducing their perception of asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…A multidimensional, integrative approach to health care should be considered when assessing patients with asthma. (23) Physicians should be aware of the fact that anxiety and depressive disorders increase the risk of poor adherence to appropriate asthma management regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health problems can impact awareness of and adherence to the treatment of asthma; thus, depression is associated with poor asthma control, which can lead to an increase in asthma exacerbations (14)(15)(16). A shift in T helper type 2 immune response due to dysregulation of the hypothalamic-pituitary-adrenal axis in response to chronic stress has been cited as a likely biological mechanism by which depression and asthma are causally related (17)(18)(19).…”
Section: At a Glance Commentarymentioning
confidence: 99%